Strong, conductive aramid fiber functionalized by graphene - Cao, Can; Peng, Jingsong; Liang, Xiumin; Saiz, Eduardo; Wolf, Stephan; Wagner, Hanoch Daniel; Jiang, Lei; Cheng, Qunfeng (Composites Part A-Applied Science and Manufacturing, 2021)
The surface modification of aramid fibers is an essential and potent approach to manipulate and improve fiber properties. Biogenic fibers are in stark contrast, as exemplified by the case of natural silk fibers. This high-performance fiber features a surface functionalization as a thin sericin film enwraps it for improving the mechanical properties of silks. Inspired by this unique sheath structure of biogenic silk, we improved the performance of aramid fibers by exploiting a coating composed of reduced graphene oxide nanosheets that self-assemble on the fiber surface guided by hydrogen bonding and π-π stacking interactions. The graphene functionalized aramid fibers show a remarkable 1 GPa improvement in tensile strength. Moreover, the functionalized aramid fiber also shows high electrical conductivity which preserved 99% of its conductivity even after 100 cycles. Our approach provides a universal strategy for improving the performance of the fiber via surface functionalization by graphene nanosheets.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Aramid fiber; Functionalized; Graphene; Interfacial interactions